Plasma dynamic synthesis of ultradispersed zinc oxide and sintering ceramics on its basis by sps method; Energy Fluxes and Radiation Effects (EFRE-2016) - Shanenkova Yu. L. Yuliya Leonidovna; Sivkov A. A. Aleksandr Anatolyevich; Ivashutenko A. S. Alexander Sergeevich; Shanenkov I. I. Ivan Igorevich; Firsov K. E. Kirill Evgenjevich (2016, 2016)
Title screen